Minimal vulvar cancer: a literature review and own observations - A. A. Il'in; A. S. Khadzhimba; S. Ya. Maksimov; I. V. Sobolev; E. A. Vyshinskaya; S. Kh. Kaitova (ABV-press, 2018)
Organ-sparing surgeries for vulvar cancer (VC) include wide excision of perineal tissues or hemivulvectomy. The advances in the treatment of VC reduce the risk of complications in patients with somatic pathology and preserve reproductive function in young patients with minimal risk of disease recurrence. The development of new approaches to VC therapy based on currently accepted clinical and morphological criteria will help to improve treatment outcomes. Materials and methods. We retrospectively analyzed the data on 252 patients with VC. Of them, 58 participants had stage I VC, 103 had stage II VC, 79 had stage III VC, and 12 had stage IV VC. The majority of patients (n = 152) underwent vulvectomy; 100 patients underwent extended vulvectomy. Results. Tumor size and depth of invasion are independent prognostic factors determining overall patient survival. The overall survival rate in patients with tumors of 1.5 cm or smaller was 91.7 %, whereas in patients with tumors >2 cm the overall survival rate was 62.2 %. Thefive-year survival rate was 53.9 % in individuals with tumor invasion >1 cm and 84.6 % in individuals with tumor invasion <0.5 cm. Conclusion. We have developed the criteria for minimal vulvar cancer: tumors <2 cm, tumor invasion <5 mm, tumors located outside theclitoris, no tumor emboli in the vessels, no multifocal growth.